DRIFT and Theoretical Studies of Ethylene/Ethane Separation on Flexible and Microporous [Cu2(2, 3‐pyrazinedicarboxylate)2(pyrazine)]n. Issue 17 (24th April 2014) - Kishida, Keisuke; Watanabe, Yumiko; Horike, Satoshi; Watanabe, Yoshihiro; Okumura, Yoshikuni; Hijikata, Yuh; Sakaki, Shigeyoshi; Kitagawa, Susumu
Abstract: The separation of olefins from paraffin is important for the production of industrial chemicals. Therefore, there is a need for a better separation system such as a pressure‐swing adsorption (PSA) process. With regard to adsorbents that enable gas separation by PSA, CPL‐1 {[Cu2 (2, 3‐pyrazinedicarboxylate)2 (pyrazine)] n } is an attractive porous material because of the flexibility and microporosity of the material, which provides it with a unique guest‐responsive nature. Adsorption isotherm studies were conducted to elucidate the ethylene‐selective adsorption properties of CPL‐1, which was further examined by breakthrough experiments with ethylene–ethane binary gas mixtures at near room temperatures. Spectroscopic and computational approaches used to investigate the interaction between CPL‐1 and the C2 gas molecules suggested that hydrogen bonds are important in the selective adsorption of ethylene over ethane. Abstract : For ethylene/ethane separation by PSA, the adsorption properties of [Cu2 (2, 3‐pyrazinedicarboxylate)2 (pyrazine)] n were investigated by both the single and binary gas system, which revealed its ethylene selective nature. Moreover, spectroscopic and computational studies suggested the importance of hydrogen bonds in the selective adsorption of ethylene over ethane.